Theoretical and Methodological Approaches of Studying the Image of China of 1931-1949 in USA Historiography - S. O. Buranok (Научный диалог, 2020)
The historiography of the problem of researching the image of China in the USA is considered. A comprehensive analysis of the evolution of the historiography of the image of China in 1931-1949 in the United States is proposed through the study of the specifics of the perception by the political elite, the military, the public and the US media of the most important events of the "Chinese crisis". It is noted that this approach allows us to talk about the formation of a special phenomenon of the socio-political life of the United States, the reconstruction and explanation of which are impossible within the framework of the traditional methodology of historical research and require an interdisciplinary approach based on historical imagology. It is shown that the formation of the image of China in 1931-1949 in the historiography of the United States by the American press is represented with several thematic areas: the first - the studies of American assessments of China in general works on the history of international relations before the Second World War and during its course; the second is a study of the history of the formation of American assistance to fighting China; third, analyzing China’s assessment of the United States in the context of the history of colonialism and decolonization; fourth, examining the image of China in the context of a study of public opinion in the United States. It is pointed out that the analysis of historiography indicates that China in the crisis period of history was in the focus of attention of both journalists and the academic community.